Implementation of Village Fund Management for Village Development and Community Empowerment in Sranak Village, Trucuk District, Bojonegoro Regency - Lestari, Siti Indah; Nugroho, Mahendra Adhi (EAJ (Economic and Accounting Journal), 2023)
The purpose of this study was to describe the implementation of village funds in Sranak Village, Trucuk District, Bojonegoro Regency. The type of research used in this study was qualitative research using descriptive-analytical research methods. This study used purposive sampling by determining several informants with predetermined criteria. The results show that implementing village funds for community development and empowerment in Sranak Village focuses on the priority of road infrastructure development so that other facilities and infrastructure needed by the community are not fulfilled.